Strengthening National Resilience in a Global Society: A Literature Review of Indonesian Digital Citizenship - Genio da Costa Martins (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rapid development of digital technology and the intensity of globalization have brought significant changes to national life, while also presenting new challenges to Indonesia's national resilience. The digital space has become a strategic arena that can strengthen or weaken national unity, depending on the quality of the community's digital citizenship. This study aims to examine the contribution of digital citizenship in supporting the strengthening of Indonesia's national resilience amidst the dynamics of global society. The method used is a qualitative approach with a literature review, through a search of national and international scientific journal articles published between 2020 and 2025 using keywords related to national resilience, digital citizenship, globalization, and citizenship education. The results of the literature review indicate that digital citizenship plays a crucial role in strengthening national resilience by improving digital literacy, digital ethics, citizen participation, and strengthening national values ​​in the digital space. Civic education and adaptive regulatory support are key factors in shaping a civilized and responsible digital society. Thus, strengthening digital citizenship is a crucial strategy for maintaining social stability, national unity, and the sustainability of Indonesia's national resilience in the global community.